PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS ACHIEVEMENT DIVISIONS (STAD) TERHADAP HASIL BELAJAR KOGNITIF FISIKA SISWA SMK N 1 RAMBAH TAHUN PEMBELAJARAN 2014/2015 - Susanti, Irna; -, Sohibun; Hatika, Rindi Genesa (Jurnal Ilmiah Mahasiswa FKIP Prodi FISIKA, 2015)
This research purposed to see the influence of cooperative learning model of STAD type. Less creativity ofteacher in teaching caused the students physic achievement still under the KKM, so it is needed anunderstanding of model which attract the interesting and motivation of students in physic. Then, increase thephysic learning cognitive result of students. This research used quantitative method. The populations were XITPHP class and XI MP of 2014/2015. Using the purposive sampling technique, XI TPHP was elected as anexperiment class and XI MP as a control class. Based on the data processing N-gain, normality, homogeneity,and analysis T-test, T value=3,07 and T table=1,996. So, H1 was accepted and H0 was refused.